TINGKAT PENGETAHUAN IBU TENTANG PENGGUNAAN ORALIT PADA BALITA DI RW 006 DESA BAGOREJO KECAMATAN SRONO KABUPATEN BANYUWANGI - Dewi - Rashati; Hadi Barru Hakam Fajar Siddiq (JURNAL ILMIAH FARMASI AKADEMI FARMASI JEMBER, 2022)
Knowledge is the result of "knowing" that occurs after someone senses a certain object. Diarrhea is the discharge of loose stools with a soft to liquid consistency with a frequency of three or more times a day. This study aims to determine the level of knowledge of mothers about the use of ORS in infants in RW 006 Bagorejo Village, Srono District, Banyuwangi Regency. The type of research used is descriptive quantitative. The method used is cross-sectional an accidental sampling of data carried out in RW 006 Bagorejo Village, Srono District, Banyuwangi Regency for the period June - July 2022 by distributing questionnaires to 72 respondents according to the inclusion criteria. Mother's level of knowledge about the use of ORS in infants in RW 006 Bagorejo Village, Srono District, Banyuwangi Regency can be seen in the categories of know, understanding, and application. Based on the results of research on 72 respondents obtained a good percentage in the know category, understanding category, and application category.